A random fatigue of mechanize titanium abutment studied with Markoff chain and stochastic finite element formulation. Issue 15 (17th November 2016) - Prados-Privado, María; Prados-Frutos, Juan Carlos; Calvo-Guirado, José Luis; Bea, José Antonio
Abstract: To measure fatigue in dental implants and in its components, it is necessary to use a probabilistic analysis since the randomness in the output depends on a number of parameters (such as fatigue properties of titanium and applied loads, unknown beforehand as they depend on mastication habits). The purpose is to apply a probabilistic approximation in order to predict fatigue life, taking into account the randomness of variables. More accuracy on the results has been obtained by taking into account different load blocks with different amplitudes, as happens with bite forces during the day and allowing us to know how effects have different type of bruxism on the piece analysed.